The interface between Master Plan and Educating Cities: an alternative for planning post-pandemic cities - Simon, Laura Panetto; Farah, Ana Paula; Merlin, José Roberto (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This research seeks to understand the possibilities of qualitative urban changes in urban space, which municipal master plans can enhance through the application of precepts outlined by the 2030 Agenda and educating cities according to the International Association of Educating Cities, conceived after the COVID-19 pandemic. Initially, this study presents and expands the tacit and informal knowledge that transforms the adjuvant urban space into the informal education process, complementary to the explicit knowledge that the official curriculum contents address. It shows that urban space, as a social instance, extrapolates its physical materiality and contains symbols and signs that enable rereading the culture that built it, also revealing historical moments and techniques that have transformed it over time, making the city an enormous classroom, decisively inducing the construction of citizenship. It evidences the advantages of treating the city planning and management from the standpoint of education for all, touching on social encounters as a way to promote alterity, politicize urban life, and exchange knowledge, noting that the Brazilian Federal Constitution requires public participation in the very preparation of master plans. Methodologically, the research supports all knowledge made explicit, presenting references from several renowned authors, and evidences some singularities of the spaces regarding the coexistence in the urban environment. During and after the pandemic, the municipal master plan, taking space as a social instance that educates for sustainability, as proposed in the 2030 Agenda, will assuredly be one of the structuring axes of quality of life in the post-pandemic period.